Application of quality by design and statistical quality control concepts in immunoassays. (December 2014) - Verch, Thorsten
Quality by design (QbD) expanded in recent years from pharmaceutical processing into analytical chemistry. Beyond online process analytical technology, off-line assays including immunoassays are also starting to benefit from QbD. Although analytical QbD is still a relatively new development, underlying concepts, such as target-oriented development and statistical quality control have been applied to diagnostic assays under the term 'design control' for several years. We reviewed how QbD and statistical quality control concepts have been applied both to diagnostic and bioanalytical immunoassays ranging from the use of individual tools to end-to-end QbD-based workflows. We will discuss some of the results of the different approaches to immunoassays, how they fit into the QbD framework and how individual tools may complement a QbD workflow.